Gestão por competências em organizações públicas: o processo de transformação organizacional e seus impactos junto aos servidores na Secretaria Estadual de Administração e Recursos Humanos (SEARH/RN) - Martins, Igor (2011)
The state has changed over time in order to meet a society with increasingly stringent demands. Techniques of private means begin to be employed in an attempt to overcome the dysfunctions entrenched bureaucracy, making the machine faster. By federal law by the People Management Skills was established as a reference for the administration of Human Resources of the public sector in an attempt to develop professionally servers, based mainly on the three pillars of the model: the knowledge, skills and attitudes. This thesis aims at understanding, in the view of employees, the perceived impacts on the organizational changes occurring in the Department of Administration and Human Resources of the State of Rio Grande do Norte in order to implement a People Management Skills-based. It is a simple case study, characterized by the research during a certain period of time, collecting data in a real environment of an organization, in this case SEARH/RN. The procedures used in collecting data were the literature review, documental research and field research. We used a qualitative approach with exploratory and descriptive approach. Every reform was implemented in the institution and reported from there analyzed the impacts observed by the servers. As a result we observed a considerable advance in institutional activities, mainly relating to physical structure / organizational and human resource policies, with minor advances on labor policies, in much the result of the guiding focus of the reform on SEARH/RN. The impacts in total were more positive than negative and direct paths to improvement in public organizations. Making a general analysis of the modernization program implemented in SEARH/RN, we can conclude that there was a distinct change in all dimensions studied, mostly pointing out positive aspects, and contrary to the opinion of some authors, who claim to be very difficult to implement reforms in public organizations, since they are highly institutionalized environments. What was found was a big organization, with gaps and weaknesses, but with a much larger number of hits and recognition from institutional actors